Prevalence studies of GB Virus-C infection using reverse transcriptase-polymerase chain reaction - Dawson, George J.; Schlauder, George G.; Pilot-Matias, Tami J.; Thiele, Dwain; Leary, Thomas P.; Murphy, Paul; Rosenblatt, Jon E.; Simons, John N.; Martinson, Francis E. A.; Gutierrez, Robin A.; Lentino, Joseph R.; Pachucki, Constance; et al. (Journal of medical virology, 1996)
Among the three recently described GB viruses (GBV‐A, GBV‐B, and GBV‐C), only GBV‐C has been linked to cryptogenic hepatitis in man. Because of the limited utility of currently available research tests to determine antibody response to GBV‐C proteins, the prevalence of GBV‐C RNA in human sera was studied using reverse transcription‐polymerase chain reaction (RT‐PCR). The prevalence of GBV‐C is higher among volunteer blood donors with elevated serum alanine aminotransferase (ALT) levels (3.9%) than among volunteer blood donors with normal ALT levels (0.8%). Higher rates were also noted among commercial blood donors (12.9%) and intravenous drug users (16.0%). GBV‐C was frequently detected in residents of West Africa, where the prevalence was >10% in most age groups. Approximately 20% of patients diagnosed with either acute or chronic hepatitis C virus (HCV) were found to be positive for GBV‐C RNA. In addition, GBV‐C RNA sequences were detected in individuals diagnosed with non‐A‐E hepatitis, with clinical courses ranging from mild disease to fulminant hepatitis. Fourteen of sixteen subjects with or without clinically apparent hepatitis were positive for GBV‐C RNA more than 1 year after the initial positive result. © 1996 Wiley‐Liss, Inc.